Impairment of Lysosome Function and Autophagy in Rare Neurodegenerative Diseases - Darios, Frédéric (J Mol Biol, 2020)
Rare genetic diseases affect a limited number of patients, but their etiology is often known, facilitating the development of reliable animal models and giving the opportunity to investigate physiopathology. Lysosomal storage disorders are a group of rare diseases due to primary alteration of lysosome function. These diseases are often associated with neurological symptoms, which highlighted the importance of lysosome in neurodegeneration. Likewise, other groups of rare neurodegenerative diseases also present lysosomal alteration. Lysosomes fuse with autophagosomes and endosomes to allow the degradation of their content thanks to hydrolytic enzymes. It has emerged that alteration of the autophagy–lysosome pathway could play a critical role in neuronal death in many neurodegenerative diseases. Using a repertoire of selected rare neurodegenerative diseases, we highlight that a variety of alterations of the autophagy–lysosome pathway are associated with neuronal death. Yet, in most cases, it is still unclear why alteration of this pathway can lead to neurodegeneration.